Divergência genética entre duas populações de Melipona scutellaris (Hymenoptera, Apidae, Meliponini) por marcadores RAPD - Campos, Ana Paula Soraggi (2000)
The stingless beekeeper (Meliponineos) can be an alternative to preserve a lot of species I m nsk of extinction, as consequence of the alterations of their habitais, besides íacihtating the scientifíc researches with this species. Uberlândia’s Meliponary was created in order to keep colonies of Melipona scutellaris (Uruçu) for beekeeper programs and biology’s researches. The colonies carne from Lençóis and Catu, both cities from the Brazilian State of Bahia. Our work analyzed the genetic divergence among the population of Uberlândia in relation to the original natural populations using molecular techniques called RAPD markers (Random Amplified Polymorphic DNA) Thirty-two arbitrary primers were tested and they revealed 136 markers RAPD allowing the separation of the populations of Melipona scutellaris with the maxim genetic dissimilaridade of 6,7%. Concerning the tested primers, II demonstrated divergence between the two populations, generating 16,2% of polimorfic bands However, the Uberlândia's Meliponary samples showed smaller genetic divergence what can be justifíed by the fact of 12 years of reproductive isolation among the original populations. The opposite was observed in the samples from Bahia, that are in permanent contact with native populations, possessing like this a great reproductive mea. The primer OPM 15 revealed a polimorfic marker, of ~ 380 pb, among the two Populations, separating them in 2 different groups (one of then corresponding to the Population of Uberlândia and the other one, to the population of Bahia). Those data suggest that this species, in the population of Uberlândia, can have been suffering some genetic alterations after its foundation. The fírst supposition is that the population-specifíc band represents an alelo that was already present in the original population, eyen so in a low rate. Once the population of Uberlândia was submitted to a small reproductive area, the proportion of this alelo in the population increased. Second, it can be happened the introduction oí different alelos in this population due to the bybridization with Melipona capixaba. The results presented in this study have a lot of aPPÜcations in relation to the population of Uberlândia and even with attempts of mcreasing the genetic variability in the population, larger efforts are necessary with eonstant introductions of new individuais and colonies of the original area. Technical RAPD was shown as a powerful tool to identify the genetic diversity among dose two Populations, detecting the variability levei among them.